Anticholinergic Drug Burden in Noncancer Versus Cancer Patients Near the End of Life - Hochman, Michael J.; Kamal, Arif H.; Wolf, Steven P.; Samsa, Greg P.; Currow, David C.; Abernethy, Amy P.; LeBlanc, Thomas W. (Journal of pain and symptom management, 2016)
Anticholinergic drugs can cause several side effects, impairing cognition and quality of life (QOL). Cancer patients are often exposed to increasing cumulative anticholinergic load (ACL) as they approach death, but this burden has not been examined in patients with nonmalignant diseases. To determine ACL and its impact in noncancer versus cancer palliative care patients. We performed a secondary analysis of 244 subjects enrolled in a randomized controlled trial. ACL was quantified with the Anticholinergic Drug Scale. We used multivariable regression to calculate the effect of ACL on key outcomes, including drowsiness, fatigue, and QOL. Patients were stratified by diagnosis, and drugs were grouped as symptom management (SM) or disease management (DM). Overall, ACL in cancer and noncancer patients was not significantly different (2.6 vs. 2.4; P = 0.23). SM drugs caused greater anticholinergic exposure than DM drugs in both cancer and noncancer patients (2.3 vs. 0.5, and 1.5 vs. 1.3, respectively; both P < 0.05); however, DM drugs exposed noncancer patients to relatively more ACL than cancer patients (1.2 vs. 0.6, P < 0.0001). ACL was associated with worse fatigue (odds ratio, 1.08; CI, 1.002–1.17) and worse QOL (odds ratio, 0.89; CI, 0.80–0.98). ACL is associated with worse fatigue and QOL and may not differ significantly between cancer and noncancer patients nearing end of life. SM drugs are more responsible for ACL in cancer and noncancer patients, although DM drugs contribute significantly to ACL in the latter group. We recommend more attention to reducing anticholinergic use in all patients with life-limiting illness.